Morphological and phylogenetic characterization of novel Metarhizium species in Guizhou, China - Chen, Wan-Hao; Han, Yan-Feng; Liang, Jian-Dong; Liang, Zong-Qi (Phytotaxa, 2019)
Two new species, Metarhizium lepidopterorum and Metarhizium rongjiangense, which are both parasitic on lepidopteran pupae, are reported. Both the morphological characteristics and DNA-based phylogenies from a multigene dataset-based analysis supported the identification of two new species. Both species can be distinguished from other species of Metarhizium by their lecanicillium-like conidiophores, longer phialides and the presence of only one type of conidium, which is smaller and fusiform in M. lepidopterorum and smaller and of subwedge shape in M. rongjiangense. The combined dataset (ITS, RPB1, RPB2 and TEF) was analysed phylogenetically in Metarhizium spp. The new species described herein are clearly distinct from other Metarhizium species.